BRCA1 promoter methylation of normal breast epithelial cells as a possible precursor for BRCA1‐methylated breast cancer. Issue 10 (1st October 2014) - Otani, Yoko; Miyake, Tomohiro; Kagara, Naofumi; Shimoda, Masafumi; Naoi, Yasuto; Maruyama, Naomi; Shimomura, Atsuhi; Shimazu, Kenzo; Kim, Seung Jin; Noguchi, Shinzaburo
<x xml:space="preserve">Abstract</x> The breast cancer susceptibility gene 1 (BRCA1) and glutathione S‐transferase P1 (GSTP1) promoters are reportedly often methylated in breast cancer tissues. Their methylation status in surrounding normal breast tissues has not been examined thoroughly although this may well be important for a better understanding of breast carcinogenesis. In this study, BRCA1 and GSTP1 promoter methylation was examined by methylation‐specific PCR assay. Patients with BRCA1‐methylated (n = 15) or BRCA1‐unmethylated (n = 15) tumors and those with GSTP1‐methylated (n = 9) or GSTP1‐unmethylated (n = 11) tumors were included in the present study. Methylation status of manually micro‐dissected normal epithelial cells from the formalin‐fixed paraffin‐embedded sections of normal breast tissues adjacent to and distant from the tumors was examined at multiple sites (n = 1–5). Of the 15 patients with BRCA1‐methylated tumors, 9 harbored BRCA1 promoter methylation in at least one site of the normal breast tissues. However, no BRCA1 promoter methylation was observed at any site of the normal tissues of the 15 patients with BRCA1‐unmethylated tumors. No GSTP1 promoter methylation was observed in the normal tissues regardless of the methylation status of the tumors. The presence of BRCA1 promoter methylation in the normal tissues was confirmed in the epithelial cells enriched with the magnetic‐activated cell sorting method. Our findings suggest that a small proportion of normal breast epithelial cells with BRCA1 promoter methylation can be precursor cells from which BRCA1‐methylated breast tumors may originate. This does not apply to GSTP1 promoter methylation.